Voltage rise due to inter-connection of embedded generators to distribution network - Mekhilef S. (2023)
This study presents voltage control method to increase embedded generation (EG) transfer capability and to ensure distribution network voltage within statutory limits. A typical EG plant and generic 11 KV distribution network was developed. Various scenarios assessed impact of embedded generator on voltage profiles of a network with light and peak load conditions.